2012
DOI: 10.1117/1.jbo.17.10.105001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ultraviolet-visible light transmission of intraocular lenses: double-beam mode versus integrating-sphere mode

Abstract: This study compared integrating-sphere and double-beam methodologies for measuring the ultraviolet/visible transmission of intraocular lenses (IOLs). Transmission spectra of control IOLs and clinically explanted IOLs were measured with an optical spectrophotometer in two optical configurations: single-beam mode with integrating sphere detector and double-beam mode with photodiode detector. Effects of temperature and surface light scattering on transmittance were measured. Effects of lens power were measured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The most common are usually around 21 diopters (D), but they can range from 10 to 30 D. This makes no difference in the case of measures performed with an integrating sphere, since in spite of the beam of light refracted by the IOL opening to a greater or lesser degree, all the radiation penetrates into the sphere and, therefore, the measurement does not depend on the power of the lens. On the other hand, as Akinay et al 13 previously reported, the effect of the IOL power can prove to be considerable in the case of DB measurements. As Fig.…”
Section: Effects Of Lens Power On Transmittancementioning
confidence: 85%
See 4 more Smart Citations
“…The most common are usually around 21 diopters (D), but they can range from 10 to 30 D. This makes no difference in the case of measures performed with an integrating sphere, since in spite of the beam of light refracted by the IOL opening to a greater or lesser degree, all the radiation penetrates into the sphere and, therefore, the measurement does not depend on the power of the lens. On the other hand, as Akinay et al 13 previously reported, the effect of the IOL power can prove to be considerable in the case of DB measurements. As Fig.…”
Section: Effects Of Lens Power On Transmittancementioning
confidence: 85%
“…All the measurements were performed at room temperature as it has already been demonstrated 13 that there is no significant variation in the result of the measurements when they are performed at room temperature 35°C. The PerkinElmer Lambda 35 spectrophotometer is accurate within AE1% transmittance, so any difference greater than 1% could be optically considered significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations